Emerging drugs in phase II and III clinical development for the treatment of alcohol use disorder - Köhne, Sophie; Hillemacher, Thomas; Glahn, Alexander; Bach, Patrick (Expert opinion on emerging drugs, 2024)
Alcohol Use Disorder (AUD) poses an ongoing significant global health burden. AUD is highly prevalent and affects not only the individuals with AUD, but also their communities and society at large. Even though pharmacotherapy is an integral part of AUD treatment, the few available substances show limited efficacy and limited clinical impact. Thus, there is a need for new innovative pharmacotherapeutic approaches. This paper provides a comprehensive review of drugs approved for the treatment of AUD as well as those currently in phase II and III development. Data from recent clinical trials has been reviewed and supplemented by additional literature based on a systematic search of the PubMed database and clinical trials registries. Compounds discussed include disulfiram, naltrexone, nalmefene, acamprosat, baclofen, sodium oxybate, doxazosin, varenicline, zonisamide, gabapentin, apremilast, ibudilast, ivermectin, tolcapone, mifepristone, suvorexant, ketamine, psilocybin, semaglutide, oxytocin and cannabidiol. Even though the majority of the discussed compounds lack sufficient evidence to support their efficacy, multiple promising new treatment options are currently under investigation. Future research has to consider specific phenotypes and subgroups of AUD as well as a possible enhancement of the effects of psychotherapy through combination with pharmacotherapy. Practitioners should be encouraged to use available compounds to support existing therapeutic regimens.
Online veröffentlicht: 18. April 2024
Gesehen am 17.09.2024